2014
DOI: 10.1002/ccd.25614
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic aortic aneurysm expansion due to late distal stent graft‐induced new entry

Abstract: Lifelong follow-up of patients is mandatory after TEVAR. A stent-graft with a tapered design should be used in aortic dissection to avoid oversizing and devastating late complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
68
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 29 publications
(59 reference statements)
3
68
0
Order By: Relevance
“…A number of studies have found that distal oversizing of the stent, in contrast, is related to distal SINE formation, 8,9,11 results similar to those in our study. Only one study reported similar oversizing in SINE and non-SINE patients, but this study included both distal and proximal SINE in the analysis and so is not comparable to the other studies.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…A number of studies have found that distal oversizing of the stent, in contrast, is related to distal SINE formation, 8,9,11 results similar to those in our study. Only one study reported similar oversizing in SINE and non-SINE patients, but this study included both distal and proximal SINE in the analysis and so is not comparable to the other studies.…”
Section: Discussionsupporting
confidence: 90%
“…However, two other reports found the taper ratio was higher in distal SINE than in non-SINE patients. 8,11 A concern when the initial insertion of the stent is distal is that before the endograft has been extended to cover the proximal tear, the pressure may build up in the false lumen and cause rupture or retrograde type A dissection. Our stents were prepared in advance, however, which decreased surgical time, and when a distal stent was used, the stent graft was smaller, so expansion of the true lumen was small.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinicians are most often confronted with difficulties in the exact measurement of aortic diameters in the acute setting of thoracic endovascular aortic repair (TEVAR), particularly in tortuosities and especially that of the aortic arch (6). Here, IVUS can be used as an important intraoperative tool to determine the exact aortic vessel diameter in TEVAR (7,8 of secondary endoleaks, and need for reintervention depend on the exact measurement of landing zones (9)(10)(11)(12), which can be especially difficult in emergency cases where no computed tomography (CT) angiography (CTA) or only CT with poor image quality is available. The objective of the present study was to validate IVUS measurements with CTA measurements in detail in a sufficiently high number of patients, which has not been previously reported.…”
Section: Introductionmentioning
confidence: 99%